2014
DOI: 10.1074/mcp.m113.033357
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Intact Flagella of Procyclic Trypanosoma brucei Cells Identifies Novel Flagellar Proteins with Unique Sub-localization and Dynamics

Abstract: Cilia and flagella are complex organelles made of hundreds of proteins of highly variable structures and functions. Here we report the purification of intact flagella from the procyclic stage of Trypanosoma brucei using mechanical shearing. Structural preservation was confirmed by transmission electron microscopy that showed that flagella still contained typical elements such as the membrane, the axoneme, the paraflagellar rod, and the intraflagellar transport particles. It also revealed that flagella severed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
202
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(212 citation statements)
references
References 88 publications
10
202
0
Order By: Relevance
“…4C,G). This dispersion is due to the heterogeneity of this cell cycle stage where the flagellum elongates from 1-2 µm to 15 µm (Sherwin and Gull, 1989a;Subota et al, 2014). The length of the old flagellum (closed red dots) was similar to cells with one flagellum (Fig.…”
Section: Ift Is Not Necessary For the Maintenance Of Flagellum Lengthmentioning
confidence: 95%
“…4C,G). This dispersion is due to the heterogeneity of this cell cycle stage where the flagellum elongates from 1-2 µm to 15 µm (Sherwin and Gull, 1989a;Subota et al, 2014). The length of the old flagellum (closed red dots) was similar to cells with one flagellum (Fig.…”
Section: Ift Is Not Necessary For the Maintenance Of Flagellum Lengthmentioning
confidence: 95%
“…Recently, another trypanosomatid-specific protein, FLAM8, was shown to localize to the distal region of the axoneme, including tips of axonemal microtubules (43), and may also be an ACS constituent. Clearly, a subset of ACS constituents is of a restricted evolutionary distribution, explaining why comparative genomic approaches failed to identify them, and possibly accounting for the morphological variations between capping structures (44).…”
Section: The Fc Is a Membrane Junction Attached By Two Types Of Kinesmentioning
confidence: 99%
“…Inducing degradation of TbFLA1 mRNA results in separation of flagellar attachment to the cell body by disrupting the flagellar attachment zone, the interface that encompasses parts of both the flagellar and cell body membranes and associated structures where the two membranes adhere (25). This disruption allows the non-adherent flagella to be sheared off the cell body and purified by differential centrifugation (26). Immunofluorescence of the transgenic BFs demonstrated that epitope-tagged TbKH was located in three discrete compartments: 1) In purified flagella, Ty1::TbKH localizes at the base of the flagella (Fig.…”
Section: Identification Of Tbkh and Subcellular Localization In Bfmentioning
confidence: 99%